Tactical urbanism: Towards an evolutionary cities' approach?. (November 2016) - Silva, Paulo
Tactical urbanism initiatives have been interpreted as an alternative and a challenge to formal spatial planning tools to the need for a more responsive planning system. Short-term implementation, scarce resources and citizens' involvement are said to be the key characteristics of this emerging movement in urbanism. In tactical urbanism, everything seems focussed on one thing: action. This paper analyses tactical urbanism initiatives in the United States considering three main aspects: the process, its interaction with planning institutions and the respective urban design outcomes. For this, the relation between tactical urbanism and complexity theory (in which self-organisation and evolution play an important role) is addressed. Findings suggest some contributions that tactical urbanism can make to urban design and spatial planning, in evolutionary terms and possible role for tactical urbanism in alternative to traditional division between plan making and plan implementation.